2003
DOI: 10.1086/378412
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Conservation and Antibody Cross‐Recognition of Clade B Human Immunodeficiency Virus (HIV) Type 1 Tat Protein in HIV‐1–Infected Italians, Ugandans, and South Africans

Abstract: We determined immune cross-recognition and the degree of Tat conservation in patients infected by local human immunodeficiency virus (HIV) type 1 strains. The data indicated a similar prevalence of total and epitope-specific anti-Tat IgG in 578 serum samples from HIV-infected Italian (n=302), Ugandan (n=139), and South African (n=137) subjects, using the same B clade Tat protein that is being used in vaccine trials. In particular, anti-Tat antibodies were detected in 13.2%, 10.8%, and 13.9% of HIV-1-infected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 51 publications
7
59
0
Order By: Relevance
“…4,63,67,84,85] and 46% of anti-Tat seropositive individuals were reported when anti-Tat ELISA were carried out with Tat variants specific for the subtype infecting patients [119]. High antibody titers directed against a broad spectrum of Tat functional domains neutralize the effects of extracellular Tat on virus replication and cell functions and play an important role in the control of the HIV infection and disease progression [105,[119][120][121][122][123][124][125][126][127][128][129][130]. Cross-sectional studies in 302 HIV-infected patients showed that anti-Tat antibodies are more frequent at the asymptomatic stage of infection compared with the symptomatic stage, whereas no differences were observed for antibodies directed against structural proteins [120].…”
Section: The Choice Of Tat As Vaccine Relevant Antigenmentioning
confidence: 99%
“…4,63,67,84,85] and 46% of anti-Tat seropositive individuals were reported when anti-Tat ELISA were carried out with Tat variants specific for the subtype infecting patients [119]. High antibody titers directed against a broad spectrum of Tat functional domains neutralize the effects of extracellular Tat on virus replication and cell functions and play an important role in the control of the HIV infection and disease progression [105,[119][120][121][122][123][124][125][126][127][128][129][130]. Cross-sectional studies in 302 HIV-infected patients showed that anti-Tat antibodies are more frequent at the asymptomatic stage of infection compared with the symptomatic stage, whereas no differences were observed for antibodies directed against structural proteins [120].…”
Section: The Choice Of Tat As Vaccine Relevant Antigenmentioning
confidence: 99%
“…It is composed of 86-101 amino acid residues (depending on the isolate) encoded by two exons. The first 72 amino acid residues (encoded by the first exon) are organized into three functional domains: (i) an acidic N-terminal region (aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] that binds to cell surface CD26 and is thought to mediate immunosuppressive activity [3]; (ii) a cysteine-rich domain (aa [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] that mediates binding to chemokine receptors [4]; and (iii) the basic domain (aa 41-60). The latter domain is responsible for the internalization of extracellular Tat and its import into the nucleus and is also required for binding to short RNA transcripts containing the viral transactivation-responsive element (TAR) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular Tat exerts a variety of biological activities that disable the immune system and permit the propagation of the virus [9]. Since Tat shows little variability among different HIV subtypes, particularly in the functional regions encoded by the first exon [10], the use of full-length Tat protein could be advantageous for therapeutic intervention. The immune system is likely to target its response to these domains, thereby preventing both Tat's extracellular action and Tat-driven transactivation inhibiting the immunosuppressive and neurotoxic properties of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that antibodies directed against the N-terminus region of Tat, which is the most immunogenic in terms of humoral responses, 32,33 protect monkeys from infection acquisition, 15 suggesting that the Tat 1-20 peptide constitutes an interesting candidate for a preventive vaccine. To assess how different routes of administration may affect humoral immunogenicity of peptide vaccines, mice were vaccinated 3 times (at days 1, 14 and 28), by ID or OM route, with Tat 1-20 peptide (EPVDPRLEPWKHPGSQPKT, synthesized by solid phase method and purified by HPLC to >98% purity by UF Peptides, University of Ferrara, Italy), encompassing an immunodominant Tat epitope, 32,33 at the dose of 7mg.…”
mentioning
confidence: 99%
“…To assess how different routes of administration may affect humoral immunogenicity of peptide vaccines, mice were vaccinated 3 times (at days 1, 14 and 28), by ID or OM route, with Tat 1-20 peptide (EPVDPRLEPWKHPGSQPKT, synthesized by solid phase method and purified by HPLC to >98% purity by UF Peptides, University of Ferrara, Italy), encompassing an immunodominant Tat epitope, 32,33 at the dose of 7mg. This dose contains the same number of molecules of 30mg of Tat protein.…”
mentioning
confidence: 99%